Radiosynthesis and in vivo evaluation of [ 11C]MP-10 as a positron emission tomography radioligand for phosphodiesterase 10A - Plisson, Christophe; Salinas, Cristian; Weinzimmer, David; Labaree, David; Lin, Shu-Fei; Ding, Yu-Shin; Jakobsen, Steen; Smith, Paul W.; Eiji, Kawanishi; Carson, Richard E.; Gunn, Roger N.; Rabiner, Eugenii A. (Nuclear medicine and biology, 2011)
The aim of this study was to evaluate a newly reported positron emission tomography (PET) radioligand [ 11C]MP-10, a potent and selective inhibitor of the central phosphodiesterase 10A enzyme (PDE10A) in vivo, using PET. A procedure was developed for labeling MP-10 with carbon-11. [ 11C]MP-10 was evaluated in vivo both in the pig and baboon brain. Alkylation of the corresponding desmethyl compound with [ 11C]methyl iodide produced [ 11C]MP-10 with good radiochemical yield and specific activity. PET studies in the pig showed that [ 11C]MP-10 rapidly entered the brain reaching peak tissue concentration at 1–2 min postadministration, followed by washout from the tissue. Administration of a selective PDE10A inhibitor reduced the binding in all brain regions to the levels of the cerebellum, demonstrating the saturability and selectivity of [ 11C]MP-10 binding. In the nonhuman primate, the brain tissue kinetics of [ 11C]MP-10 were slower, reaching peak tissue concentrations at 30–60 min postadministration. In both species, the observed rank order of regional brain signal was striatum>diencephalon>cortical regions=cerebellum, consistent with the known distribution and concentration of PDE10A. [ 11C]MP-10 brain kinetics were well described by a two-tissue compartment model, and estimates of total volume of distribution ( V T) were obtained. Blocking studies with unlabeled MP-10 revealed the suitability of the cerebellum as a reference tissue and enabled the estimation of regional binding potential ( BP ND) as the outcome measure of specific binding. Quantification of [ 11C]MP-10 binding using the simplified reference tissue model with cerebellar input function produced BP ND estimates consistent with those obtained by the two-tissue compartment model. We demonstrated that [ 11C]MP-10 possesses good characteristics for the in vivo quantification of the PDE10A in the brain by PET.